Brief Report: Effect of CMV and HIV Transcription on CD57 and PD-1 T-Cell Expression During Suppressive ART. (1st June 2016) - Dan, Jennifer M.; Massanella, Marta; Smith, Davey M.; Spina, Celsa A.; Schrier, Rachel; Daar, Eric S.; Dube, Michael P.; Morris, Sheldon R.; Gianella, Sara
Abstract : Abstract: HIV-infected men who have sex with men are nearly universally coinfected with cytomegalovirus (CMV). In this study of 45 HIV-infected men who have sex with men virologically suppressed on ART, we found that presence of seminal CMV DNA shedding and higher levels of systemic cellular HIV RNA transcription were both independently associated with increased PD-1 expression on circulating CD4 + T cells, but not with higher levels of senescent (CD57 + ) T cells. In addition, greater HIV RNA transcription was associated with lower CD57 expression on CD8 T cells. Although causality cannot be inferred from this retrospective study, these results suggest that asymptomatic CMV replication and residual cellular HIV transcription may contribute to persistent immune dysregulation during suppressive ART. Abstract : Supplemental Digital Content is Available in the Text.